Analysis of short- and long-run interactions between real exchange rate and private domestic investment in South Africa. (2017) - Maepa, Magdeline M.; Muzindutsi, Paul-Francois
This study analysed the short- and long-run interactions between the real exchange rate and private domestic investment in South Africa, during the period of a free-floating exchange rate system. Vector autoregressive (VAR) model, a multivariate Johansen co-integration approach and Granger causality test were used to analyse quarterly observations from 1994 to 2014. Co-integration analysis found no evidence supporting the long-run relationship between real exchange rate and private domestic investment in South Africa. However, short-run analysis showed that both variables are mostly driven by their own innovation with short-run changes in real exchange rate being affected by changes in private domestic investment. Granger causality test found a one-way causal relationship from private domestic investment to real exchange rate; implying that previous changes in private domestic investment lead to changes in current real exchange rate. This study concluded that growth in South African private domestic investments is linked with the depreciation of the domestic currency.